Growth performance, phytate degradation, and tibia characteristics of broiler chickens fed pelleted diets with varying feed particle sizes and phytase levels - Stephanie Wolfrum; Maria Francesch; Beatriz Jimenez-Moya; Dieter Feuerstein; Markus Rodehutscord (Journal of Applied Poultry Research)
Summary: The objective was to investigate the effects of feed particle size and microbial phytase supplementation of pelleted diets on growth performance, myo-inositol hexakisphosphate (InsP6) degradation, and tibia characteristics in broiler chickens. Ross 308 broilers were housed in 56 floor pens in groups of 42, and seven pens were allocated to one of eight dietary treatments to measure the performance data on day 38 of age. From day 21 to 26, six birds from each floor pen were moved to metabolism units with the same distribution of treatments for digestibility and bone measurements. For the starter phase, two diets with fine or coarse particle size (429 or 657 µm mean particle size, determined after feed processing by wet sieving) were formulated and added with 500 FTU phytase/kg. For the grower and finisher phase, diets were arranged with two particle sizes (fine and coarse, 434 or 729 µm) and four phytase levels (0, 300, 600, and 1,200 FTU/kg). No significant interactions between particle size and phytase were determined. Prececal InsP6 disappearance and P digestibility were higher with fine than coarse particles, indicating that coarse grinding of rapeseed meal may not benefit birds. Increasing phytase supplementation increased ADG, ADFI, prececal InsP6 disappearance and P digestibility, tibia ash, and tibia breaking strength. Under the conditions of this study, birds were sufficiently supplied with P at a total P level of 4.0 g/kg and phytase supplementation of 1,200 FTU/kg. Renouncement of feed phosphate in the grower and finisher phase was possible without impaired performance.